Altered hypoxia‐inducible factor–1α (HIF‐1α) signaling contributes to impaired angiogenesis in fetal lambs with persistent pulmonary hypertension of the newborn (PPHN) - Makker, Kartikeya (Physiol Rep, 2019)
Previous studies in adult pulmonary hypertension reported that increased hypoxia‐inducible factor–1α (HIF‐1α) signaling contributes to pulmonary vascular remodeling. However, alterations in endothelial HIF‐1α signaling and its contribution to impaired angiogenesis in persistent pulmonary hypertension of the newborn (PPHN) remain unclear. We investigated the hypothesis that HIF‐1α levels are increased in lung endothelial cells in PPHN and contribute to impaired angiogenesis function. We examined HIF‐1α expression and promoter activity in the isolated pulmonary artery endothelial cells (PAEC) from fetal lambs with or without PPHN induced by prenatal ductus arteriosus constriction. We measured the levels of HIF‐1α downstream targets, vascular endothelial growth factor (VEGF) and glycolytic protein, hexokinase 2 (Hek‐2) in PAEC from PPHN, and control lambs. We examined the effect of small interfering‐RNA (siRNA) mediated knockdown of native HIF‐1α on VEGF expression and in vitro angiogenesis function of PPHN‐PAEC. HIF‐1α protein levels were higher in the isolated PAEC from PPHN‐lambs compared to controls. HIF‐1α promoter activity and Hek‐2 protein levels were higher in PPHN. VEGF protein levels and in vitro angiogenesis function were decreased in PAEC from PPHN lambs. HIF‐1α silencing significantly increased the expression of VEGF and improved the angiogenesis function of PPHN PAEC. Aberrant HIF‐1α signaling contributes to endothelial dysfunction and decreased angiogenesis in PPHN.